A study on Problems faced by Women Entrepreneurs in Kasaragod District, Kerala with special reference to ‘Prakrithi women -led business in Bedakam Panchayat. - C.K.Reji, Dr.V.Chitra (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
In today’s entrepreneurship plays a crucial role in GDP growth by driving innovation, creating jobs etc. For fostering economic development, entrepreneur's identify opportunities, establish business and contribute to productivity leading to increased output and economic expansion. Among the total population in India, 14.4% are engaged in entrepreneurial activity (According to GEM India report). In fact, among that, the majority are men entrepreneurs. Women ‘s participation are only 14%. Women entrepreneur's also play vital role for economic development by contributing GDP growth and social progress. Encouraging and supporting women in business leads to increase innovation, diversify economic activity, job creation etc. It also helps to empower women economically and socially, fostering a more inclusive and equitable society. The paper mainly focused on (i)to find out the problems faced by women entrepreneurs in current scenario, (ii) To know the influence level of government and local authority among the development of women entrepreneurship, (iii)to analyse challenges and opportunities faced by women entrepreneurship. The study involves both primary and secondary data. Primary data was collected by distributing questionnaire and collected data is presented in the form of table.